Aplikasi Mesin Pencuci dan Rotary Dryer untuk Peningkatan Nilai Tambah Produk Empon-Empon di Desa Bandar, Kecamatan Bandar, Pacitan - Fea Prihapsara; Okid Parama Astirin; Endang Siti Rahayu; Anif Nur Artanti (Universitas Mathla'ul Anwar Banten, 2022)
APLICATION OF WASHING MACHINE AND ROTARY DRYER FOR INCREASING ADDED VALUE VALUE OF EMPON-EMPON IN BANDAR VILLAGE, BANDAR DISTRICT, PACITAN. Bandar Village is located in Bandar District, Pacitan Regency. The economy of the people in Bandar Village is supported by traditional medicinal plants, especially empon-empon as the main commodity. Most of the farmers in Bandar Village are small farmers who depend on selling their crops to middlemen. The middlemen argue that prices at the farm level are low because the empon-empon is still dirty. The aim of this project is to carry out post-harvest processing activities by applying of washing machine and rotary dryer to increase the added value of the empon-empon products. Washing machine can clean it from dirt while rotary dryer can reduce the water content thereby increasing the yield of the active ingredients of empon-empon. Currently, both machines can function properly. This transfer of technology is very helpful for farmers in processing their harvested products on a large scale and they can sell them at higher prices. Kelompok Tani Suroloyo I as a partner actively participated in this project from post-harvest processing to marketing. This project is carried out on an ongoing basis in collaboration between Pusat Penelitian Lingkungan Hidup Universitas Sebelas Maret Team (PPLH UNS) and Kelompok Tani Suroloyo I.